Transformation : Jung's legacy and contemporary clinical work today - Cavalli, Alessandra; Hawkins, Lucinda; Stevns, Martha (Karnac Books, 2014)
The book offers a challenging reading of the legacy of C.G. Jung, who offered fascinating insights into the psyche but did not provide a theoretical framework for clinical work. Thus, clinicians are faced with both the richness and lacunae of Jung's legacy and how to work with it. This challenge is taken up by distinguished post-Jungian thinkers from Britain, Europe and the US who, in fertile contact with psychoanalysis, reassess Jung's work and propose new tools for clinical practice. By looking anew at concepts such as maternal containment, affect, ego formation and ego strength, infantile.